MASS-CUSTOMIZED OUTPATIENT APPOINTMENT RULE GENERATOR - Ki, Youngmin; Kim, Byung-In (International Journal of Industrial Engineering: Theory, Applications and Practice, 2019)
This study claims that if a mass-customized appointment rule is developed for each individual outpatient doctor, it could improve the performance and service quality of outpatient clinics. A simulation-based optimization algorithm is proposed for mass-customized appointment rule generation. Various environmental factors, such as preferred appointment intervals, new and return patients, no-shows, walk-in patients, stochastic consultation times, and patient unpunctuality, are considered to generate implementable and practical rules. The simulation-based optimization algorithm uses several well-known appointment rules as initial solutions, evaluates the effectiveness of rules by simulation that considers practical environmental factors, improves rules using a neighborhood search, and reports the best rule. The algorithm generates a variable-block-size/fixed-interval rule consisting of the numbers of new and return patients in each appointment interval. Computational experiments show that the proposed algorithm can generate effective appointment rules with user-provided preferred appointment interval considering the various environmental factors.